The Representation and Perception of Roman Imperial Power Proceedings of the Third Workshop of the International Network Impact of Empire (Roman Empire, c. 200 B.C. - A.D. 476), Rome, March 20-23, 2002 - de Blois, Lukas; Erdkamp, Paul; Hekster, Olivier; de Kleijn, Gerda; Mols, Stephan (Impact of Empire, 2003)
Ancient history: to c 500 CE